The Effect of Meloxicam Nanocrystal Formation with the Addition of PVP K-60 and Decyl Glucoside as Stabilizers on Its Solubility - Titta Hartyana Sutarna; Tika Meilina; Nur Achsan Al-Hakim (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2025)
Meloxicam (MLX) is a non-steroidal anti-inflammatory drug that has low bioavailability when administered orally due to its low solubility, and efforts have been made to improve drug delivery to improve solubility. The aim of this study was to prepare and characterize Meloxicam nanocrystals (MLX-NC) and evaluate them with the addition of polyvinylpyrrolidone K-60 (PVP K-60) and decyl glucoside (DG) to prevent nanoparticle aggregation. MLX-NC preparation by a combination of ultrasonic homogenization and the freeze-drying method. The particle size analysis results ranged from 9.76 to 12.73 nm with a polydispersity index <0.5, indicating a homogeneous and stable size distribution. PXRD and DSC characterization revealed the disappearance of the characteristic crystalline peaks of MLX, indicating a transformation to an amorphous form. Additionally, based on saturated solubility studies, the solubility of MLX-NC increased by up to 173 times compared to pure MLX. This study shows that the formulation, initially intended as nanocrystals, resulted in an amorphous solid dispersion due to the influence of stabilizer concentration. This transformation, along with reduced particle size, contributed synergistically to the enhanced solubility of MLX.